SPEAKING ABOUT WASTING TIME - Maxmudxo’jayeva Ziyodaxon Isomitdinovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Introduction Time  is  one of  the most  valuable  resources  in human  life. Unlike  money  or material possessions, time cannot be earned back once it is lost. Every person has the same twenty-four hours in a day, but people use this time differently. Some individuals spend their time productively, while others waste it on unimportant activities. Wasting time  has  become  a  common  problem  in  modern  society  due  to  the  influence  of technology,  social  media,  and  poor  planning.  Understanding  the  causes  and consequences of wasting time can help people manage their lives more effectively. What Does Wasting Time Mean? Wasting time means spending time on activities that do not bring meaningful results or help achieve personal goals. It does not mean that every minute must be spent working. Rest, hobbies, and entertainment are important parts of life. However, time becomes wasted when people spend excessive amounts of it on activities that provide little value. For example, many people spend hours scrolling through social media without learning anything useful. Others procrastinate by watching videos, playing games, or chatting  online  when  they  should  be  studying  or  working. These  habits  may  seem harmless at first, but over time they can lead to serious problems.